Enhancing Community Economic Independence through Capacity-Building Training Services: The Mediating Role of MSME Development Strategies - Deva Putra A; Dede Irman Pirdaus; Rifki Saefullah (International Journal of Research in Community Services, 2026)
The role of Micro, Small, and Medium Enterprises (MSMEs) in strengthening community economic independence has become increasingly important, particularly in developing countries. However, many MSMEs still face challenges related to limited managerial capacity, low financial literacy, and ineffective business strategies. This study aims to analyze the effect of capacity-building training services on community economic independence, with MSME development strategies acting as a mediating variable. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships among variables. The results indicate that capacity-building training services have a significant positive effect on MSME development strategies and community economic independence. Furthermore, MSME development strategies significantly influence economic independence, demonstrating their role in improving business performance and sustainability. The mediation analysis reveals that MSME development strategies partially mediate the relationship between training services and economic independence, indicating that training becomes more effective when translated into practical business strategies. This study highlights the importance of integrating training programs with strategic implementation to achieve sustainable economic outcomes. The findings provide both theoretical and practical contributions by emphasizing the role of strategy as a key mechanism in transforming capacity building into economic independence. Therefore, policymakers and practitioners are encouraged to design training programs that focus not only on knowledge transfer but also on the development of actionable business strategies.